Efficient container stacking approach to improve handling: efficiency in Chinese rail–truck transshipment terminals. (January 2020) - Li, Wang; Xiaoning, Zhu; Zhengyu, Xie
An efficient container stacking approach is vital to the handling efficiency of container transshipment terminals. In this paper, by considering container allocation preferences and operation distance, the container stacking problem in rail–truck transshipment terminals has been formulated as a multi-objective optimization model to minimize container overlapping amounts and crane moving distance. A simulation-based algorithm implementing process has been developed to stack containers to the optimum positions. Computational experiments on data from a rail–truck transshipment terminal in China are conducted to test the efficiency of the proposed approach. Experimental results demonstrate that the container stacking approach is efficient and significant for improving handling efficiency in rail–truck transshipment terminals.